The Influence Of Interaction On Student Satisfaction Via Flow Experience Among Distance Learners - Kassim, Siti Fatimah Mohd (2023)
Lifelong learning has been recognized as a global priority for addressing the many challenges of sustainability in the Malaysia Education Blueprint 2015 - 2025. Correspondingly, in an online setting, learners have fewer possibilities to interact with higher education institutions. Despite several studies on interactions, flow, and student satisfaction, it is relevant to Western countries and traditional students. The study aims to investigate the impact of interactions (learner-content, learner- instructor, and learner-learner) on student satisfaction among distance learners in Malaysia. The research framework in this study is based on the transactional distance theory proposed by Moore (1989). To test the proposed hypotheses, data was collected through the self-administered questionnaire tool, Survey Monkey. The study sample consisted of 270 respondents that conform to the inclusion criteria, and SPSS was used to analyze the hypotheses. This study found a favorable and substantial association between flow experience and student satisfaction. Meanwhile, the hypotheses' results show that learner-content, learner-instructor, and learner- learner interaction each have a positive impact on student satisfaction. Finally, the further three hypotheses tested did not indicate that learner-content interaction, learner-instructor interaction, and learner-learner interaction have a significant impact on flow experience. Several theoretical and practical implications of the study are explored based on the study's findings, methodologies, and results. Suggestions for future research are also offered.